Quality care during labour and birth: a multi-country analysis of health system bottlenecks and potential solutions. (December 2015) - Sharma, Gaurav; Mathai, Matthews; Dickson, Kim; Weeks, Andrew; Hofmeyr, G; Lavender, Tina; Day, Louise; Mathews, Jiji; Fawcus, Sue; Simen-Kapeu, Aline; de Bernis, Luc
Abstract Background Good outcomes during pregnancy and childbirth are related to availability, utilisation and effective implementation of essential interventions for labour and childbirth. The majority of the estimated 289, 000 maternal deaths, 2.8 million neonatal deaths and 2.6 million stillbirths every year could be prevented by improving access to and scaling up quality care during labour and birth. Methods The bottleneck analysis tool was applied in 12 countries in Africa and Asia as part of theEvery Newborn Action Plan process. Country workshops engaged technical experts to complete the survey tool, which is designed to synthesise and grade health system "bottlenecks", factors that hinder the scale up, of maternal-newborn intervention packages. We used quantitative and qualitative methods to analyse the bottleneck data, combined with literature review, to present priority bottlenecks and actions relevant to different health system building blocks for skilled birth attendance and basic and comprehensive emergency obstetric care. Results Across 12 countries the most critical bottlenecks identified by workshop participants for skilled birth attendance were health financing (10 out of 12 countries) and health workforce (9 out of 12 countries). Health service delivery bottlenecks were found to be the most critical for both basic and comprehensive emergency obstetric care (9 out of 12 countries); health financing was identified as having critical bottlenecks for comprehensive emergency obstetric care (9 out of 12 countries). Solutions to address health financing bottlenecks included strengthening national financing mechanisms and removing financial barriers to care seeking. For addressing health workforce bottlenecks, improved human resource planning is needed, including task shifting and improving training quality. For health service delivery, proposed solutions included improving quality of care and establishing public private partnerships. Conclusions Progress towards the 2030 targets for ending preventable maternal and newborn deaths is dependent on improving quality of care during birth and the immediate postnatal period. Strengthening national health systems to improve maternal and newborn health, as a cornerstone of universal health coverage, will only be possible by addressing specific health system bottlenecks during labour and birth, including those within health workforce, health financing and health service delivery.